Rancang Bangun Sistem Multi-Sensor Untuk Pengukuran Jarak Secara Simultan - Idang Wahyuddin Septiawan; Sabriansyah Rizqika Akbar; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
A multi-sensor system that runs simultaneously is a factor to be considered when building a multi-sensor system. In order for the system to run simultaneously required a system with a fast response. By applying multitasking then the system can execute more than one program simultaneously. RTOS (Real Time Operating System) is one method for multitasking application on embedded system. To implement RTOS into Arduino requires FreeRTOS library. Arduino Mega 2560 Microcontroller and HC-SR04 sensor module as much 8. Communication interface on this system using Parallel Bus Interface (PBI) to support performance in multisensor system running simultaneously. In the application of RTOS this system will be divided into 8 tasks. Each task will process each of the HC-SR04 sensor modules. From the results of performance testing HC-SR04 sensor module gain percentage error of 0% of all sensors. For testing the execution time stability of each task is 1ms on each task in 10 experiments. From the test results, the system that runs the RTOS running from the beginning of the program to the end requires a total time of 8.1332ms average while on systems that do not implement RTOS requires a total time average of 264ms. Each task has an execution time ranging from 1.005 to 1.583ms.